Incidence Rate of Advanced Chronic Kidney Disease Among Privately Insured Adults with Neurodevelopmental Disabilities - Whitney DG; Schmidt M; Bell S; Morgenstern H; Hirth RA (Clinical Epidemiology, 2020)
Daniel G Whitney,1,2 Mary Schmidt,1 Sarah Bell,1 Hal Morgenstern,3– 5 Richard A Hirth2,6,7 1Department of Physical Medicine and Rehabilitation, University of Michigan, Ann Arbor, MI, USA; 2Institute for Healthcare Policy and Innovation, University of Michigan, Ann Arbor, MI, USA; 3Department of Epidemiology, School of Public Health, University of Michigan, Ann Arbor, MI, USA; 4Department of Environmental Health Sciences, School of Public Health, University of Michigan, Ann Arbor, MI, USA; 5Department of Urology, School of Medicine, University of Michigan, Ann Arbor, MI, USA; 6Department of Health Management and Policy, University of Michigan School of Public Health, Ann Arbor, MI, USA; 7Department of Internal Medicine, University of Michigan, Ann Arbor, MI, USACorrespondence: Daniel G Whitney Tel +1 734-936-7175Email dgwhit@umich.eduPurpose: Due to complex medical profiles, adults with neurodevelopmental disabilities (NDDs) may have a heightened risk for early development of chronic kidney disease (CKD) and accelerated CKD progression to advanced stages and kidney failure. The purpose of this study was to estimate the incidence rate of advanced CKD for adults with NDDs and compare the incidence rate to adults without NDDs.Patients and Methods: Data were used from the Optum Clinformatics® Data Mart to conduct this retrospective cohort study. The calendar year 2013 was used to identify eligible participants: individuals ≥ 18 years of age and without advanced CKD. Participants were followed from 01/01/2014 to advanced CKD, loss to follow-up, death, or end of the study period (12/31/2017), whichever came first. Diagnostic, procedure, and diagnosis-related group codes identified NDDs (intellectual disabilities, cerebral palsy, autism spectrum disorders), incident cases of advanced CKD (CKD stages 4+), diabetes, cardiovascular diseases, and hypertension present in the year 2013. Crude incidence rates (IR) of advanced CKD and IR ratios (IRR), comparing adults with vs without NDDs (with 95% CI) were estimated. Then, Cox regression estimated the hazard ratio (HR and 95% CI) for advanced CKD, comparing adults with NDDs to adults without NDDs while adjusting for covariates.Results: Adults with NDDs (n=33,561) had greater crude IR of advanced CKD (IRR=1.32; 95% CI=1.24– 1.42) compared to adults without NDDs (n=6.5M). The elevated rate of advanced CKD among adults with NDDs increased after adjusting for demographics (HR=2.19; 95% CI=2.04– 2.34) and remained elevated with further adjustment for hypertension and diabetes (HR=2.01; 95% CI=1.87– 2.15) plus cardiovascular disease (HR=1.84; 95% CI=1.72– 1.97). Stratified analyses showed that the risk of advanced CKD was greater for all NDD subgroups.Conclusion: Study findings suggest that adults with NDDs have a greater risk of advanced CKD than do adults without NDDs, and that difference is not explained by covariates used in our analysis.Keywords: chronic kidney disease, neurodevelopmental disabilities, intellectual disabilities, cerebral palsy, autism spectrum disorders